Sistem Informasi Kependudukan Data Masyarakat Kantor Kecamatan Parung - Muhammad Ifdal Alfirli; Revih Tri Al Fachrizel; Cuntoko Prastio; Sirilus Daeli; Rohmy Dimyati; Yustin Kurniawan Harefa; Agung Wijoyo (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
In the early era, the use of information technology was felt to be very important for government actors to facilitate work and produce information quickly. The Parung District Office is engaged in recording population data for the community and in that case we feel the importance of using this information technology. In the current system, this sub-district has difficulties in processing or making data recording reports. In overcoming these problems, research has been carried out, namely building a population information system for population data. With the existence of a population data information system, it is hoped that it will facilitate and speed up the Parung sub-district in processing and making reports on community population data.